Torosaurus is not Triceratops: ontogeny in chasmosaurine ceratopsids as a case study in dinosaur taxonomy. - Nicholas R Longrich (Public Library of Science (PLoS), 2012)
Background In horned dinosaurs, taxonomy is complicated by the fact that the cranial ornament that distinguishes species changes with age. Based on this observation, it has been proposed that the genera Triceratops and Torosaurus are in fact synonymous, with specimens identified as Torosaurus representing the adult form of Triceratops. The hypothesis of synonymy makes three testable predictions: 1) the species in question should have similar geographic and stratigraphic distributions, 2) specimens assigned to Torosaurus should be more mature than those assigned to Triceratops, and 3) intermediates should exist that combine features of Triceratops and Torosaurus. The first condition appears to be met, but it remains unclear whether the other predictions are borne out by the fossil evidence. Methodology/principal findings We assessed the relative maturity of Torosaurus and Triceratops specimens by coding skulls for characters that vary with maturity, and then using a clustering analysis to arrange them into a growth series. We found that a well-defined sequence of changes exists in horned dinosaurs: development of cranial ornament occurs in juveniles, followed by fusion of the skull roof in subadults, and finally, the epoccipitals, epijugals, and rostral fuse to the skull in adults. Using this scheme, we identified mature and immature individuals of both Torosaurus and Triceratops. Furthermore, we describe the ventral depressions on the frill of Triceratops, and show that they differ in shape and position from the parietal fenestrae of Torosaurus. Thus, we conclude that these structures are not intermediates between the solid frill of Triceratops and the fenestrated frill of Torosaurus. Conclusions/significance Torosaurus is a distinct genus of horned dinosaur, not the adult of Triceratops. Our method provides a framework for assessing the hypothesis of synonymy through ontogeny in the fossil record.